JENNIFER M. BOSCO & ANGELA CHUANG (2018) A new species of grass spider, Agelenopsis riechertii, from the Southwestern USA, with notes on its courtship behavior (Araneae: Agelenidae). Zootaxa, 4442: 579–583. - Bosco, Jennifer M.; Chuang, Angela (Zootaxa, 2018)
We made changes in the description of a new Agelenopsis spider species, Agelenopsis riechertae. Firstly, we declare the male holotype and a type repository to validate the species description, which was previously omitted. The original Latin name has been feminized from Agelenopsis riechertii to Agelenopsis riechertae.